Exploring Factors Contributing to Graduate Outcomes: Using Career Registration Methodology (CRM) to Track Students’ Employability Activities, Career Readiness, and Graduate Outcomes - Serene Lin-Stephens; Luella C. Leon; Maurizio Manuguerra; Tasos Barkatsas; Leoni Russell (Education Sciences)
Graduate outcomes are a key indicator of university performance, yet the progression of students in career preparation during university is ill-understood. The Career Registration Methodology (CRM) addresses this gap by tracking students’ career planning and participation in employability and professional experiences (EPEs) throughout their university enrolment. This research used CRM to monitor students’ employability development and career readiness, assessing their impact on graduate outcomes. By analysing longitudinal CRM data and Graduate Outcomes Survey (GOS) results from 1653 students, this study examined how EPEs and career readiness influenced full-time employment, job offers, the perceived value of qualifications, and perceptions of overqualification. Correlation and trend analyses revealed positive associations between career readiness over time and employment outcomes, with regression analyses identifying EPEs as the most significant factor. Practical implications of the findings highlight CRM’s value in aiding higher education institutions, especially Work Integrated Learning (WIL) and Career Development Learning (CDL) educators, to identify trends and tailor support whilst students are still in the university. As the first CRM study in Australia based on the first available cohort, the exploratory nature of this research is acknowledged along with recommendations to refine periodic, non-intrusive measurements such as CRM for enhanced validity and reliability.